2012
DOI: 10.1021/ol302136c
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Cross-Coupling of N-Heterocyclic Chlorides and Bromides with Arylmagnesium Reagents

Abstract: A simple, practical iron salt catalyzed procedure allows fast cross-couplings of N-heterocyclic chlorides and bromides with various electron-rich and -poor arylmagnesium reagents. A solvent mixture of THF and tBuOMe is found to be essential for achieving high yields mainly by avoiding homocoupling side reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 82 publications
0
35
0
Order By: Relevance
“…Nakamura et al reported a selective biaryl synthesis based on iron(III) fluoride catalyzed cross-coupling of aryl chlorides with aryl Grignard reagents where the fluoride ion remarkably suppresses the homocoupling in presence of additive like 1,3-bis(2,6-diisopropylphenyl)imidazolinium chloride (SIPr.HCl) [30]. Very recently Knokhel and co-workers reported iron(III) bromide mediated coupling of N-heterocyclic chlorides and bromides with arylmagnesium bromide lithium chloride complex [31]. Herein, we report the formation of cross-coupled biaryls along with homo-coupled products through iron(III) chloride catalyzed reactions of aryl Grignard reagents and aryl halides without using any additives.…”
Section: Introductionmentioning
confidence: 92%
“…Nakamura et al reported a selective biaryl synthesis based on iron(III) fluoride catalyzed cross-coupling of aryl chlorides with aryl Grignard reagents where the fluoride ion remarkably suppresses the homocoupling in presence of additive like 1,3-bis(2,6-diisopropylphenyl)imidazolinium chloride (SIPr.HCl) [30]. Very recently Knokhel and co-workers reported iron(III) bromide mediated coupling of N-heterocyclic chlorides and bromides with arylmagnesium bromide lithium chloride complex [31]. Herein, we report the formation of cross-coupled biaryls along with homo-coupled products through iron(III) chloride catalyzed reactions of aryl Grignard reagents and aryl halides without using any additives.…”
Section: Introductionmentioning
confidence: 92%
“…Sulfamate and carbamate functional groups could be used as directing groups for various synthetic transformations in iron-catalyzed cross-couplings due to their high stability, easy availability, and low reactivity toward conventional Pd(0) catalyzed methods (Scheme 119a). Recently, Knochel and co-workers (163) developed iron-catalyzed sp 2 -sp 2 cross-coupling between N-heterocyclic chlorides/bromides and arylmagnesium reagents (Scheme 119b). …”
Section: B Aryl Derivatives As Coupling Partnersmentioning
confidence: 99%
“…But, its related complex 159 (Scheme 209, Scheme 210) was air stable but unable to show activity toward reductive amination. Interestingly, when it was treated with trimethylamine N-oxide, which oxidatively removed CO ligand from 159 and generated a 16e species (163,Scheme 211). Subsequently, 163 reacted with hydrogen to form 130 in situ, which showed full conversions with moderate yield and selectivity.…”
Section: Reductive Aminationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] However, these species must imperatively be manipulated under inert and anhydrous conditions, which complicates their use in parallel chemistry. To the best of our knowledge, the most general methods for the transfer of aryl and heteroaryl units onto azines and diazines are those of Knochel [12,13] and Quéguiner. [14] However, as these procedures involve organomagnesium reagents, sensitive groups such as aldehydes and ketones cannot be present on either coupling partner.…”
Section: Introductionmentioning
confidence: 99%